Concepção das deficiências entre os povos indígenas yanomami e waiwai : um olhar do pesquisador, do profissional da saúde e do educador - Machado, Giselle Ferraz (2016)
This study aims to analyze the conception of people waiwai and yanomami on disability and its impact on the socio-cultural practices and the lives of people with disabilities, according to the researcher's view, according to the cultural exchange level of waiwai ethnicities and yanomami in Roraima state. Therefore, it was defined as specific objectives: to study cosmology, beliefs, religion and rituals of the birth of indigenous people with disabilities; identify bioethical conflicts and biopower mechanisms in relation to persons with disabilities in the communities studied; analyze policies and practices of primary health care for people with disabilities in indigenous territories and analyze educational policies and inclusion of indigenous people with disabilities in this system. Due to the complexity of the topic, considerations in anthropology, bioethics and cultural intervention, biopower and a brief history of indigenous resistance movements were included. Obtaining these data was both through literature review and through interviews, in which professionals responded to pre-established questions by the author. Under the gaze of professional cultural exchange with indigenous waiwai and yanomami, the disabled individual is still in a vulnerable situation, especially in communities with lower relationship with non-Indians. This situation reveals worrying not only by the lack of knowledge and resources to deal with the disabled person, but the design that have disability therefore not amenable to care or treatment, even in communities with the presence of health workers or teachers basic education. It is essential to guarantee the fundamental rights the establishment of intercultural dialogue.